Discussion of Accounting Measurement, Price-Earnings Ratios, and the Information Content of Security Prices - Larcker, David F. (Journal of Accounting Research, 1989)
David F. Larcker, Discussion of Accounting Measurement, Price-Earnings Ratios, and the Information Content of Security Prices, Journal of Accounting Research, Vol. 27, Current Studies on The Information Content of Accounting Earnings (1989), pp. 145-152